Cognitive Empathy: A Key Learning Modality For Era 5.0 - Mirna Ari Mulyani; Aprilia Setyowati; Irfan Fahriza; Ayu Yusaeni (Journal of Education and Counseling (JECO), 2025)
Learning in the era of society 5.0 is oriented towards the character and ability of students to behave prosocially amid technological convenience. However, many students are not fully able to integrate cognitive abilities and empathy in social interactions. This research aims to formulate the dimensions of cognitive empathy that support learning success in the 5.0 era, as well as identify relevant guidance activities in the development of cognitive empathy. The research method employed a Systematic Literature Review of 8 Scopus articles that met the inclusion criteria. The results of the study reveal the dimensions of cognitive empathy that are crucial for learning success in the 5.0 era, namely perspective-taking, contextual understanding, rational and ethical thinking, and human-centered problem-solving. Alternative guidance can use narrative media, technology-based interactive simulations (including AI), and design thinking training, all of which focus on developing pro-social perspectives and actions.